“You Can’t Eat Prestige”:[1] A Consideration of Unionization in the Museum Sector - Johnna Henry (Washington University Journal of Law and Policy, 2024)
Today’s museum workers are rapidly unionizing—a major shift in pace in the fifty-year history of museum unionization efforts; moreover, contemporary efforts to unionize and bargaining goals differ in many ways from the first museum workers’ unionization movements of the 1970s. This Note argues that the narrowing scope of the “mandatory bargaining subjects” in the National Labor Relations Act creates difficulty for art museum unions to focus bargaining efforts on issues impacting the professional nature of museum work, which has distinctly shaped museum unionization goals today. Efforts to unionize museum workers are important to the labor community because they generate legal commentary on collective bargaining issues and provide transparency for the social and economic hardships of museum workers, especially those industry hardships stemming from the COVID-19 pandemic. Since the inception of the labor movement, the National Labor Relations Board and courts have narrowed their interpretation of the “mandatory bargaining subjects” for which employers and unionized workers are required to collectively bargain under the National Labor Relations Act. Narrow interpretations of “mandatory bargaining subjects” have impacted museum workers’ ability to bargain for a stronger voice in decision-making at the managerial level, and contribute to the grounding of these efforts instead in bargaining over wages, workplace safety, job security, and benefits. Contemporary unionization efforts by museum workers seek to highlight the value of museum work while exposing—and remedying—barriers to employment, inadequate compensation, lack of opportunity for advancement, and availability of employment.
Keywords: MuseumUnionization; CollectiveBargaining; LaborRights; MuseumWorkers; WorkplaceEquity